IMPLEMENTATION OF THE PRINCIPLES OF INTERNAL BALANCE BUYING AND BUYING LAND - Widodo, Sigit; Endang Retnowati; Agam Sulaksono (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
ABSTRAC Land is an asset that is really needed by society, where human needs for land will continue to increase, and accessibility to land is increasingly limited. The need for land is monetary, social and mechanical. Land registration is a prerequisite in efforts to organize and regulate the allocation, control, ownership and use of land, including to resolve various land problems. Land registration is intended to provide certainty of rights and legal protection for holders of land rights by proving a land certificate, as a controlling instrument in the use and benefits of land. The transfer of land rights due to sale and purchase should be carried out before the PPAT by making a binding sale and purchase agreement in accordance with Government Regulations. Number 24 of 1997 concerning Land Registration in the practice of buying and selling land, buying and selling is based on the power contained in the land sale and purchase agreement, so the researcher wrote about "Implementation of the Principle of Balance in Land Buying and Selling". The formulation of the main problem in this research is about how the principle of balance in the sale and purchase of land is implemented and what is the legal position of sellers and buyers in the sale and purchase of land with the research objective being to analyze the implementation of the principle of balance to what extent it is applied in making land sale and purchase agreements. As well as to analyze the legal position of the Seller and Buyer in the Sale and Purchase of Land to prevent violations of the implementation of the principle of balance in the sale and purchase of land. This research is normative legal research, or a literature review of legal provisions. Secondary Legal Materials, specifically provide explanations of primary legal materials such as research results, the work of the legal community, and so on. It is a scientific method for determining truth based on normative logic and using law as its object. The absence of norms, unclear norms, and conflicting norms are the forerunners of normative legal research. By looking for the benefits of implementing the Principle of Balance in buying and selling land, it provides legal protection for the rights and responsibilities of executors, namely sellers and buyers, in carrying out land buying and selling transactions by binding themselves to each other. Apart from that, the application of the principle of balance is explained in the formulation of the rights and obligations of the parties, as a determining indicator of the explanation it appears in the balanced position between the rights and obligations of each party in the land sale and purchase agreement and the implementation of the Principle of Balance in the Sale and Purchase of Land is a form of giving each other their rights. each buyer-seller and the responsibility of each buyer-seller in carrying out and implementing the Land Sale and Purchase Agreement in the hope that there will be no disputes in the future. Keywords: Land, Buying and Selling, Balance, Seller, Buyer